Rice husk biochar influences seedling emergence of junglerice (Echinochloa colona) and herbicide efficacy - Chauhan, Bhagirath S. (Scientific Research Publishing, Inc., 2013)
The use of carbonized rice husk biochar improves the fertility and productivity of poor soils in rice-based cropping systems. However, biochar may also influence weed seedling emergence and the efficacy of soil-applied herbicides. Experiments were conducted in a screenhouse to evaluate the effect of biochar rates (0, 20, 40, and 80 t·ha?1) and seed burial depth (0, 1, and 2 cm) on seedling emergence of junglerice (Echinochloa colona) and the effect of biochar rates and pendimethalin (0, 500, 1000, and 1500 g·a.i.·ha?1) and pretilachlor doses (0, 300, 600, and 900 g·a.i.·ha?1) on seedling emergence and seedling biomass of junglerice. Data were analyzed using nonlinear regression. The burial depth to inhibit 50% of maximum seedling emergence was 0.76 cm when biochar was not added to soil and the depth increased with an increase in biochar rates for soil. Similarly, compared with the soil with no biochar, the use of bichoar increased the pretilachlor dose to inhibit 50% of maximum emergence or biomass. The pretilachlor dose to inhibit 50% of maximum biomass of junglerice was 100, 130, 240, and 240 g·ha?1 when biochar was added at 0, 20, 40, and 80 t·ha?1. However, the efficacy of pendimethalin was not influenced by biochar rate. The results of this study suggest that rice husk biochar may increase weed seedling emergence from deeper burial depths and may decrease the efficacy of some soil-applied herbicides.